309 A FRAILTY CENSUS OF INPATIENTS AGED 65 AND OVER ADMITTED TO A MODEL 4 HOSPITAL. (25th October 2022) - Carroll, I; O'Connor, M; Cunningham, N; Ryan, S; Corey, G; McNamara, D; Galvin, R; Sheikhi, A; Shannahan, E; Mastalska, A; Dillon, J; Barry, L
Abstract: Background: Frailty is a risk factor for in-hospital mortality, long hospital stay and functional decline at discharge. Profiling the prevalence and level of frailty within the acute hospital setting is vital to ensure evidence-based practice and service development within the construct of frailty. Methods: All patients aged ≥65 years and admitted to a medical or surgical inpatient setting, were screened over a 12-hour period (08:00-20:00) using validated frailty and co-morbidity scales. Age and Gender Demographics, Clinical Frailty Scale (CFS), Charlson Co-morbidity Index (CHI) and admitting specialty (Medical/Surgical) were collected. The data was fully anonymised and ethical approval was granted. Descriptive statistics were used to profile the cohort and Chi-squared tests applied for comparisons. Results: Within a sample of 413 patients, 291(70%) were ≥65yrs. Of this cohort, 202(70%) were ≥75yrs. 207(71%) utilised in-patient medical services and 121(41%) surgical services while 37(12%) used both. The mean CFS was 6 indicating moderate frailty levels and the mean CCI score was 4 denoting moderate co-morbidity. Overall: 195(67%) had moderate-severe frailty (CSF ≥6) while 218 (75%) had moderate-severe co-morbidity (CCI Mod 3-4, Severe ≥5). Associations with age >75 and frailty (p=0.001) and medical service usage and frailty (p=0.004) were established. No significant differences were observed across genders for CFS (p=0.110) and CCI (p=0.465). Conclusion: There is a high prevalence of frailty and co-morbidity within the admitted patient cohort ≥65yrs. Overcrowding across the hospital system and higher levels of frailty and comorbidity will contribute to increased lengths of stay and the need for specialist intervention, particularly for those ≥75yrs who represented 70% of patients screened. With an increased focus on the integration of care for older adults across care transitions, there is a clear need for expansion of frailty-based services and staff training in frailty care across the hospital and community setting.